Peningkatan Kapasitas Masyarakat Peri-urban Kota Semarang dalam Pengolahan Sampah Organik Rumah Tangga - Fariz, Trida Ridho; Marianti, Aditya; Susilo, Bambang Eko; Wahyuni, Siti; Widiarti, Nuni; Sukaesih, Sri; Al Hakim, M. Faris; Sari, Virgania; Maulana, Faith Miftah; Setiyanda, Karista Gadis (Universitas Negeri Semarang, 2025)
The peri-urban area of Semarang City, particularly Pakintelan Village, Gunungpati District, has experienced rapid residential growth over the past decade. However, this growth has not been accompanied by adequate waste management infrastructure, especially for household organic waste. Many residents still dispose of or burn organic waste such as food scraps and vegetables, which negatively impacts the environment and public health. To address this issue, this community service initiative aimed to enhance residents' capacity to process organic waste into environmentally friendly and economically valuable products. The methodology involved in-depth interviews with neighborhood leaders to identify key issues, followed by a literature review to develop educational materials, and concluded with practical training on producing eco-enzyme from household kitchen waste. The program ran smoothly and received enthusiastic participation from the community. Residents showed a strong interest in applying eco-enzyme production in their daily lives. Moving forward, further research is recommended on developing a community-based organic waste management system, as not all residents have the space or time to process waste independently